2017
DOI: 10.1016/j.ceb.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated regulation of heterochromatin

Abstract: The formation of condensed, transcriptionally repressed heterochromatin is essential for controlling gene expression throughout development, silencing parasitic DNA elements, and for genome stability and inheritance. Cells employ diverse mechanisms for controlling heterochromatin states through proteins that modify DNA and histones. An emerging theme is that chromatin-associated RNAs play important roles in regulating heterochromatin proteins by controlling their initial recruitment to chromatin, their stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…The RITS complex uses base pairing interactions between the loaded siRNA and nascent transcripts (along with H3K9me2 interactions) to localize to pericentric regions. Localized RITS complexes recruit histone methyltransferases, leading to H3K9 methylation, HP1 recruitment (Swi6 in S. pombe ), heterochromatic silencing, and generation of more siRNAs through recruitment of Dicer and an RNA-dependent RNA polymerase (RdRP) [ 327 , 328 ]. In this way, heterochromatin is maintained through a self-reinforcing positive feedback loop; siRNA promotes H3K9 methylation which promotes siRNA production, and both siRNA and H3K9me2 interact with the RITS complex to facilitate its localization to pericentric heterochromatin [ 327 , 328 ].…”
Section: Changing Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RITS complex uses base pairing interactions between the loaded siRNA and nascent transcripts (along with H3K9me2 interactions) to localize to pericentric regions. Localized RITS complexes recruit histone methyltransferases, leading to H3K9 methylation, HP1 recruitment (Swi6 in S. pombe ), heterochromatic silencing, and generation of more siRNAs through recruitment of Dicer and an RNA-dependent RNA polymerase (RdRP) [ 327 , 328 ]. In this way, heterochromatin is maintained through a self-reinforcing positive feedback loop; siRNA promotes H3K9 methylation which promotes siRNA production, and both siRNA and H3K9me2 interact with the RITS complex to facilitate its localization to pericentric heterochromatin [ 327 , 328 ].…”
Section: Changing Conceptsmentioning
confidence: 99%
“…Like in fission yeast, small RNAs contribute to heterochromatin regulation in fungi, ciliates, plants, and worms acting through RNA-dependent RNA polymerase (RdRP) , self-reinforcing feedback loops and histone methylation [ 327 , 328 ]. In plants, in addition to histone methylation, siRNAs also direct the methylation of the DNA from which they derived [ 329 ].…”
Section: Changing Conceptsmentioning
confidence: 99%
“…Similarly, the preferential way of the chromatin networking might be determined by the anisotropic (symmetry breaking) super-packaging of heterochromatin [54], with its aggregation-stimulating capacity to impinge 'a sticky silence' on the large genome domains [15,55]. The non-coding RNA that is transcribed from heterochromatin [56] can also electrostatically contribute to its packaging [25,57]. The spatial compartmentalization of the nucleus is maintained by relatively simple basic physicochemical principles, including electrostatic and hydrophobic forces that generate an extremely detailed 'nuclear topology' giving a material basis to robust gene expression regulation, as indicated by Ronald Hancock [58].…”
Section: The Genome "Maps" Of Positional Information Need Phase Transmentioning
confidence: 99%
“…The advent of technologies to profile RNA-protein interactions has demonstrated that DNA-binding factors associate with RNAs to regulate transcriptional and post-transcriptional processes (9 -11). Although the functional role of RNA in chromatin organization has been a focus of previous work (12,13), recent studies have uncovered interactions between RNA and proteins, including long noncoding RNAs (lncRNAs), which influence chromatin structure by binding and regulating activity of chromatin modifying enzymes (14 -18). Xist is an example of a lncRNA that facilitates chromatin organization by interacting with epigenetic repressors to inactive one X chromosome in female mammalian cells (19).…”
mentioning
confidence: 99%